2017
DOI: 10.1007/s10930-017-9729-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Dihydroorotase from Methanococcus jannaschii

Abstract: The gene that codes for the putative dihydroorotase in the hyperthermophilic archaeon Methanococcus jannaschii was subcloned in pET-21a and expressed in Escherichia coli. A purification protocol was devised. The purity of the protein was evaluated by SDS-PAGE and the protein was confirmed by sequencing using LC-MS. The calculated molecular mass is 48104 Da. SEC-LS suggested that the protein is a monomer in solution. ICP-MS showed that there are two Zn ions per monomer. Kinetic analysis of the recombinant prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 41 publications
(66 reference statements)
3
22
0
Order By: Relevance
“…In addition, dihydroorotase was found to be essential for the survival of S. aureus [42]. Similar findings were also introduced in Gram-negative bacteria by others [40]. Moreover, this enzyme is equally essential in fungal cell metabolism [43].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, dihydroorotase was found to be essential for the survival of S. aureus [42]. Similar findings were also introduced in Gram-negative bacteria by others [40]. Moreover, this enzyme is equally essential in fungal cell metabolism [43].…”
Section: Discussionsupporting
confidence: 66%
“…The crystal structure of the dihydroorotase from E. coli was determined and it was found that the active site contains two zinc ions, which are bridged by a hydroxide group or a water molecule [39]. Structural studies confirmed the prediction that dihydroorotase is a member of the amidohydrolase superfamily with a (βα)8-barrel protein fold [39,40]. Several publications have investigated the role of inhibition of dihydroorotase in both Gram-positive and Gram-negative bacteria, which indicated its ubiquitous distribution and applicability as a suitable target for antimicrobial drug discovery.…”
Section: Discussionmentioning
confidence: 74%
“…The protein used was the same as in the earlier study and the preparation procedure was described in that paper (Vitali et al 2017). The dihydroorotase activity in the biosynthetic direction was studied in 100 mM Mes pH 5.8 by measuring the dihydroorotate formed per minute at 230 nm, ε230 nm = 1.17 mM -1 cm -1 (Washabaugh and Collins 1984) using substrate concentrations to 9.08 mM.…”
Section: Methodsmentioning
confidence: 99%
“…A previous physicochemical characterization of Mj DHOase gave insight into its similarities and differences from the DHOases of the other types and subtypes (Vitali et al 2017). Mj DHOase is a monomer-unlike most DHOases that form dimers-and is most similar to the bacterial type I DHOase from Bacillus anthracis (Ba DHOase).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation